Productivity and quality improvement in electronics assembly - Edosomwan, Johnson A. (McGraw-Hill, 1988)
This book provides useful backround information and selected papers on specialized topic areas in electronics assembly. Users of this handboook shoud follow these steps to enhance their knowwledge in the various topics covered.